Essential trauma management training: addressing service delivery needs in active conflict zones in eastern Myanmar - Richard Matthew G; Lee Catherine I; Richard Allison J; Oo Eh; Lee Thomas; Stock Lawrence (BMC, 2009)
Abstract Introduction Access to governmental and international nongovernmental sources of health care within eastern Myanmar's conflict regions is virtually nonexistent. Historically, under these circumstances effective care for the victims of trauma, particularly landmine injuries, has been severely deficient. Recognizing this, community-based organizations (CBOs) providing health care in these regions sought to scale up the capacity of indigenous health workers to provide trauma care. Case description The Trauma Management Program (TMP) was developed by CBOs in cooperation with a United States-based health care NGO. The goal of the TMP is to improve the capacity of local health workers to deliver effective trauma care. From 2000 to the present, international and local health care educators have conducted regular workshops to train indigenous health workers in the management of landmine injuries, penetrating and blunt trauma, shock, wound and infection care, and orthopedics. Health workers have been regularly resupplied with the surgical instruments, supplies and medications needed to provide the care learnt through TMP training workshops. Discussion and Evaluation Since 2000, approximately 300 health workers have received training through the TMP, as part of a CBO-run health system providing care for approximately 250 000 internally displaced persons (IDPs) and war-affected residents. Based on interviews with health workers, trauma registry inputs and photo/video documentation, protocols and procedures taught during training workshops have been implemented effectively in the field. Between June 2005 and June 2007, more than 200 patients were recorded in the trauma patient registry. The majority were victims of weapons-related trauma. Conclusion This report illustrates a method to increase the capacity of indigenous health workers to manage traumatic injuries. These health workers are able to provide trauma care for otherwise inaccessible populations in remote and conflicted regions. The principles learnt during the implementation of the TMP might be applied in similar settings.